2017
DOI: 10.1097/ccm.0000000000002642
|View full text |Cite
|
Sign up to set email alerts
|

Delirium and Catatonia in Critically Ill Patients: The Delirium and Catatonia Prospective Cohort Investigation*

Abstract: Objective Catatonia, a condition characterized by motor, behavioral and emotional changes, can occur during critical illness and appear as clinically similar to delirium, yet its management differs from delirium. Traditional criteria for medical catatonia preclude it’s diagnosis in delirium. Our objective in this investigation was to understand the overlap and relationship between delirium and catatonia in ICU patients and determine diagnostic thresholds for catatonia. Setting Convenience cohort, nested with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(35 citation statements)
references
References 30 publications
1
34
0
Order By: Relevance
“…Additionally, the patient was inattentive, disoriented, and had generalized slowing on EEG, consistent with a diagnosis of delirium. These findings reinforce recent research that shows that delirium and catatonia can coexist, despite the DSM-V criteria that preclude the diagnosis of both conditions concurrently(6).…”
supporting
confidence: 89%
“…Additionally, the patient was inattentive, disoriented, and had generalized slowing on EEG, consistent with a diagnosis of delirium. These findings reinforce recent research that shows that delirium and catatonia can coexist, despite the DSM-V criteria that preclude the diagnosis of both conditions concurrently(6).…”
supporting
confidence: 89%
“…An intensive care unit–based study found that about a third of patients with delirium have catatonia and patients with more signs of catatonia are more likely to have delirium. 25 It has been pointed out that some of the ICSD-5 diagnostic criteria for delirium 2 ( Table 1 ) can paradoxically result in the underdiagnosis of delirium. 16 For example, diagnosing delirium is forbidden in the presence of an arousal disorder that precludes assessment of attention and cognition.…”
Section: Discussionmentioning
confidence: 99%
“…Another important distinction that must be made in this case is between postictal delirium (occurring in 35% of seizure cases and reported to last sometimes up to 10 days) [ 25 27 ] and postictal catatonia as it may substantially influence treatment decision-making [ 28 30 ]. Whereas benzodiazepines are used first in cases of catatonia, in delirium such compounds may aggravate symptoms [ 28 30 ]. The distinction between the two may be cumbersome given clinical overlap.…”
Section: Discussionmentioning
confidence: 99%
“…The distinction between the two may be cumbersome given clinical overlap. According to the DSM-5 it is impossible for the two to co-occur since catatonia cannot be diagnosed in the presence of delirium; others question this notion [ 30 ]. In addition, Grover [ 28 ] found that 12 to 30% of patients with delirium showed symptoms matching the criteria for catatonia.…”
Section: Discussionmentioning
confidence: 99%